1999
DOI: 10.1001/archderm.135.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Cryogen Spray Cooling in Combination With Nonablative Laser Treatment of Facial Rhytides

Abstract: Background: Cryogen spray cooling can be used to provide epidermal protection while still achieving spatially selective photocoagulation in the upper dermis. The objective of this study is to determine the efficacy and safety of cryogen spray cooling in combination with a nonablative Nd:YAG (= 1320 nm) laser treatment of facial rhytides in human volunteers. Observations: Thirty-five adults with bilateral periorbital rhytides were treated with cryogen spray cooling in combination with 3 nonablative laser treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 209 publications
(138 citation statements)
references
References 7 publications
(6 reference statements)
3
135
0
Order By: Relevance
“…The irradiation sources included a 1.32 mm Nd:YAG laser [8,9], Er:glass laser (1.54 mm) [10], or non-coherent pulsed light source [11], applied in combination with either CSC or a contact cooling device. All these modalities utilize relatively weakly absorbed radiation, which enables heat deposition deep into the dermis, and active cooling of the skin surface.…”
Section: Introductionmentioning
confidence: 99%
“…The irradiation sources included a 1.32 mm Nd:YAG laser [8,9], Er:glass laser (1.54 mm) [10], or non-coherent pulsed light source [11], applied in combination with either CSC or a contact cooling device. All these modalities utilize relatively weakly absorbed radiation, which enables heat deposition deep into the dermis, and active cooling of the skin surface.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, controlled dermal heating without epidermal damage is achieved by combining the laser or intense pulsed-light treatment with the simultaneous cooling of the skin surface [9]. The selective thermal damage of the dermis is followed by a wound healing response from the damaged tissue, which ultimately leads to new collagen formation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown efficacy in the treatment of atrophic facial scars with only mild edema and erythema post-procedure. 45,46 A study comparing the 1320 nm Nd:YAG to the 1450 nm diode laser for treatment of atrophic acne scars revealed that the 1450 nm laser effected more significant change in the scar appearance and skin texture. 46 Both mid-infrared lasers, however, induced clinical improvement.…”
Section: 45mentioning
confidence: 99%